Erastin-induced ferroptosis enhances natural killer cell anti-tumor activity and offers therapeutic potential in neuroblastoma - Anthonydhason, Vimala; Islamagic, Erna; Leijon, Nikki; Gaarder, Jennie; Martinsson, Tommy; Fransson, Susanne; Thorén, Fredrik B; Umapathy, Ganesh (Frontiers in Immunology, 2026)
High-risk neuroblastoma (NB) often relapses and becomes refractory to treatment, making it a significant contributor to childhood cancer mortality despite its relative rarity. Addressing the challenges posed by NB’s resistance to conventional apoptosis-inducing therapies (e.g., chemotherapy and radiation) has become a pressing concern in pediatric oncology research. In recent years, the growing comprehension of alternative cell death modalities distinct from apoptosis has revealed a promising avenue in the endeavor to combat treatment-resistant cancers. One such mechanism, ferroptosis, has attracted increasing attention for its potential role in combating therapy-resistant cancer cells. High-risk NB typically exhibits an immune-excluded phenotype, characterized by minimal immune cell infiltration. Despite this characteristic, the mechanisms underlying immune exclusion and impaired immune activation in NB remain unclear. Here, we demonstrate that the induction of ferroptosis using Erastin, a cystine-glutamate antiporter inhibitor, reduces NB cell proliferation and foci formation. Furthermore, our transcriptomics analysis revealed that treatment with Erastin in NB cells led to increased expression of ULBP1, a ligand to the activating natural killer (NK) cell receptor, NKG2D. Upon ferroptosis induction, the transcription factor ATF4 was found to drive ULBP1 expression in NB cells. Consistent with this, pre-treatment with Erastin sensitized NB cells to NK cell cytotoxicity in co-culture experiments. These results suggest the NK cell’s cytotoxic function can be enhanced with Erastin-mediated ferroptosis, which may be beneficial for NB patients.